2D Transition Metal Carbides (MXenes): Applications as an Electrically Conducting Material. Issue 51 (4th November 2020) - Shahzad, Faisal; Iqbal, Aamir; Kim, Hyerim; Koo, Chong Min
Abstract: Since their discovery in 2011, 2D transition metal carbides, nitrides, and carbonitrides, known as MXenes, have attracted considerable global research interest owing to their outstanding electrical conductivity coupled with light weight, flexibility, transparency, surface chemistry tunability, and easy solution processability. Here, the promising abilities of 2D MXenes, from both experimental and theoretical perspectives, for designing conductive materials for a range of applications, including electromagnetic interference shielding, flexible optoelectronics, sensors, and thermal heaters, are presented. Abstract : The excellent metallic conductivity of MXenes has elevated them to the forefront of a wide range of applications. The performance of highly conductive MXenes is comparable to that of conductive metals, and superior to many carbon‐based nanomaterials for electromagnetic shielding, conducting electrodes, sensors, and thermal heaters. A brief overview of the mentioned application areas is presented.